Pelatihan Teatrikal Puisi pada Anak dan Remaja Sektor Sion Jemaat Passo Utara Tahun 2025 - Pattipeiluhu, Lisse; Umkeketony, Sarleoki Nancy (Universitas Pattimura, 2025)
Community service activities in collaboration with the GPM Passo Utara Congregation. This community service aims to increase creativity, self-confidence, and the ability to appreciate children's and adolescent literature through theatrical poetry training. The training was carried out in the Zion Sector of the Passo Utara Congregation in 2025, involving participants aged 10–14 years. The benefits of this activity are expected to enable participants to implement theatrical poetry performances. The methods used include providing theoretical knowledge about poetry, practicing vocal techniques, intonation, expression, and appreciation, and ending with a performance as an evaluation of the results of the theatrical poetry training. The results of the training showed an increase in the participants' ability to express themselves through theatrical poetry, growing courage to appear in public, and building a spirit of togetherness among children and adolescents. Thus, this activity not only contributes to the development of artistic talent but also forms character and strengthens positive values within the GPM Passo Utara congregation. The output of the activity was a theatrical poetry performance entitled